TLR3 or TLR4 Activation Enhances Mesenchymal Stromal Cell-Mediated Treg Induction via Notch Signaling. (20th September 2016) - Rashedi, Iran; Gómez-Aristizábal, Alejandro; Wang, Xing-Hua; Viswanathan, Sowmya; Keating, Armand
Abstract : Mesenchymal stromal cells (MSCs) are the subject of numerous clinical trials, largely due to their immunomodulatory and tissue regenerative properties. Toll-like receptors (TLRs), especially TLR3 and TLR4, are highly expressed on MSCs and their activation can significantly modulate the immunosuppressive and anti-inflammatory functions of MSCs. While MSCs can recruit and promote the generation of regulatory T cells (Tregs), the effect of TLR activation on MSC-mediated Treg induction is unknown. In this study, we investigated the effect of ligand-mediated activation of TLR3 and TLR4 on Treg induction by human MSCs. We found that generation of Tregs in human CD4(+) lymphocyte and MSC cocultures was enhanced by either TLR3 or TLR4 activation of MSCs and that the increase was abolished by TLR3 and TLR4 gene-silencing. Augmented Treg induction by TLR-activated MSCs was cell contact-dependent and associated with increased gene expression of the Notch ligand, Delta-like 1. Moreover, inhibition of Notch signaling abrogated the augmented Treg levels in the MSC cocultures. Our data show that TLR3 or TLR4 activation of MSCs increases Treg induction via the Notch pathway and suggest new means to enhance the potency of MSCs for treating disorders with an underlying immune dysfunction, including steroid resistant acute graft-versus-host disease.